The validation of a new development screening tool for developmental delays among HIV-Infected South African children - Boyede, Ojombo Gbemisola (Department of Paediatrics and Child Health, 2015)
Background: Over 50% of HIV-infected children in South Africa have developmental delays. Early identification of affected children will lead to early intervention and favourable long-term outcome. Screening for developmental delay is not yet routine by many primary healthcare providers due to lack of locally available, rapid and sensitive screening tool s in busy Paediatric HIV clinics. A new screening tool was developed at the Red Cross War Memorial Children's Hospital (RCWMCH) for detecting moderate to severe global developmental delay among very young HIV infected children. The diagnostic accuracy and usefulness of the new tool was evaluated in this study. Objective: to validate the new RCWMCH developmental screening too l among HIV - infected South African children. Method: Forty-seven HIV-infected children in the age category 9-36 months attending the Infectious Disease Clinic (IDC) of the RCWMCH were screened using the new tool. Full developmental assessments of same children were performed using the Bayley Scale of Infant Development (BSID - III). Developmental Delay (global) was defined as composite scores 2 standard deviations below the mean in two or more developmental domains. Results: The sensitivity of the RCWMCH tool was 78.5%, specificity 54.6%, positive predictive value was 42.6%, and negative predictive value was 85. 7 %. Discussion: The RCWMCH screening tool was found to have sensitivity within the acceptable levels recommended for developmental screening tools. Its high negative predictive value will reduce unnecessary referrals for full developmental assessments in asymptomatic infants and toddlers. It is therefore recommended for screening for developmental delay among HIV-infected children from the age of 9 months to 3 years.